PENGARUH PROMOSI KESEHATAN MENGGUNAKAN MEDIA LEAFLET TERHADAP PENGETAHUAN IBU HAMIL TERHADAP PEMERIKSAAN HEMOGLOBIN (Hb) PADA TRIMESTER I DAN TRIMESTER III DI PUSKESMAS TARERAN - Kristina Hariyani; Widia Shofa Ilmiah (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
Hemoglobin is a component of red blood cells responsible for distributing oxygen throughout the body. Decreased hemoglobin levels can lead to anemia. One of the health problems that can occur in pregnant women is a decrease in hemoglobin (Hb) levels. Anemia in pregnant women has a bad impact on the mother and fetus. Possible adverse effects on pregnant women include longer labor, bleeding during childbirth, and shock. Adverse effects on the fetus include premature birth, low birth weight, disability, and even infant death. Anemia during pregnancy is defined as a disease in which hemoglobin (Hb) levels in the body are below the normal value of 10 g/dL. Knowledge about pregnancy is one of the factors that affect the high maternal mortality rate. This study aims to determine the effect of health promotion using leaflet media on pregnant women's knowledge of hemoglobin (Hb) examination in the first and third trimesters at the Tareran Health Center. This type of research is a quantitative research with a pre-experimental design through one group pre-post test design. The population of this study is all pregnant women in the first, second, and third trimesters. The population of this study amounted to 85 people with a purposive sampling technique and a research sample of 30 respondents was obtained. The results of this research use the Wilcoxon Signed Rank Test. Based on the results of the study, a significance value of p-value 0.000 < 0.05 was obtained, which means that there was an effect of health promotion using leaflet media on pregnant women's knowledge of hemoglobin (Hb) examination in the first and third trimesters at the Tareran Health Center.